Exploring Student Discipline in Private Madrasah Aliyah: Insights, Strategies and Challenges - Suci Ramadhani; Nurika Khalila Daulay (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2024)
This article aims to describe the insights, challenges, and student discipline strategies implemented by the deputy head of the madrasah to make it even better. This research uses qualitative research with a grounded theory approach. Data collection was carried out using interviews, observation, and documentation. Data analysis includes data reduction, data presentation, and conclusion. Data validity is guaranteed through credibility, transferability, dependability, and confirmability. The research results show that: 1) a Description of student discipline mainly focusing on punctuality and dressing, 2) the strategy of the deputy head of the madrasah in instilling the value of discipline in students, including providing examples, habituation, giving advice, and giving sanctions, 3) the challenges faced by the deputy head of the madrasah in instilling the values of discipline student including students' lack of self-awareness and the influence of the external environment. The research implication is that the deputy head of the madrasah is essential in instilling disciplinary values, ultimately positively impacting student achievement and overall school success.